2012
DOI: 10.1371/journal.pntd.0001730
|View full text |Cite
|
Sign up to set email alerts
|

Fine Scale Spatiotemporal Clustering of Dengue Virus Transmission in Children and Aedes aegypti in Rural Thai Villages

Abstract: BackgroundBased on spatiotemporal clustering of human dengue virus (DENV) infections, transmission is thought to occur at fine spatiotemporal scales by horizontal transfer of virus between humans and mosquito vectors. To define the dimensions of local transmission and quantify the factors that support it, we examined relationships between infected humans and Aedes aegypti in Thai villages.Methodology/Principal FindingsGeographic cluster investigations of 100-meter radius were conducted around DENV-positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 34 publications
5
102
1
Order By: Relevance
“…The study in Thailand using RT-PCR to detect the dengue virus in mosquitoes also showed a positive association between infected Ae. aegypti and dengue-infected children [68]. That study demonstrated the occurrence of an infected mosquito prior to the reporting of the index case(s).…”
Section: Discussionmentioning
confidence: 98%
“…The study in Thailand using RT-PCR to detect the dengue virus in mosquitoes also showed a positive association between infected Ae. aegypti and dengue-infected children [68]. That study demonstrated the occurrence of an infected mosquito prior to the reporting of the index case(s).…”
Section: Discussionmentioning
confidence: 98%
“…Improved methods for detection of DENV RNA or antigen in mosquitoes (Bangs et al 2007, Chao et al 2007, Chen et al 2010, Tan et al 2011, Muller et al 2012, Voge et al 2013) provide new opportunities for mosquito-based DENV surveillance, and studies focusing entirely or in part on dengue patient premises have shown promise with regards to the potential for linking DENV infections in Ae. aegypti to human dengue cases in space and time (Pinheiro et al 2005, Urdaneta et al 2005, García-Rejón et al 2008, Guedes et al 2010, Yoon et al 2012). Despite a substantial effort – including monthly indoor backpack aspiration mosquito collections from a large number of homes (typically >125 per month) scattered over ~30 neighborhoods in Mérida City, and with nearly 5,800 Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Active surveillance of human infections can be efficiently achieved using geographical cluster sampling around dengue index cases. 25,26 Here, ‘index case’ refers to the laboratory-diagnosed clinical dengue case that initiates a cluster investigation within a geographically restricted area around the home of a person with a documented DENV infection. Geographical cluster investigations could be used to compare the fine-scale spatial signature of DENV transmission in areas with and without Wolbachia (Figure 2).…”
Section: A Pragmatic Approach To Optimize Wolbachia Deploymentmentioning
confidence: 99%
“…aegypti mosquitoes is challenging because of the low infection rates (typically ~0.1%) in the adult females across the population, although infection rates can be higher in locations of geographical cluster investigations. 25 Because mosquitoes that test positive for virus are not necessarily infectious, the proportion of DENV-infected mosquitoes does not directly translate into an estimate of virus transmission unless virus disseminated from the mosquito midgut or in saliva is also assayed, and even this approach is limited by the sensitivity of assays and variation of in vitro saliva collections. Nonetheless, a successful intervention is expected to reduce the incidence of viremic and infectious humans and, therefore, similarly reduce the incidence of DENV infection in mosquitoes in areas where Wolbachia infection predominates.…”
Section: A Pragmatic Approach To Optimize Wolbachia Deploymentmentioning
confidence: 99%